Designing a Culture-Based Learning Model: A Qualitative Exploration for Strengthening Local Identity in Primary Education - Sri Sugiyarti; Mukminan Mukminan; Sujarwo Sujarwo (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2024)
In an era of globalization, the erosion of local cultural identity among young learners presents a critical challenge for educational systems. This study addresses this gap by designing a comprehensive culture-based learning model aimed at strengthening the local identity of primary school students. Employing a qualitative exploratory case study design, data were collected from five elementary schools in Sleman, Yogyakarta, through in-depth interviews with principals, teachers, students, and community stakeholders, complemented by classroom observations and document analysis. The findings culminate in a three-pillar Culture-Based Learning Model: (1) Curricular Integration, embedding local wisdom (e.g., Javanese folklore, language) and experiential arts (e.g., batik, gamelan) into core subjects; (2) Structured Extracurricular Programs for deeper cultural immersion; and (3) the creation of a Culturally Responsive School Environment. The model is operationalized through implementation strategies emphasizing community collaboration and digital technology, alongside a robust tripartite evaluation mechanism assessing cognitive understanding, attitudinal pride, and practical skills. The study demonstrates that systematic cultural integration fosters early internalization of local values, builds resilience against global homogenization, and strengthens community-school ties. This research provides educators and policymakers with a theoretically grounded and actionable framework for designing learning ecosystems that effectively preserve cultural heritage while nurturing culturally confident students.